PENGARUH PEMBERIAN KURMA AJWA (Phoenix dactylifera) TERHADAP PERUBAHAN TEKANAN DARAH IBU HAMIL HIPERTENSI - Husaidah, Siti; Ikhtiar, Muhammad; Nurlinda, Andi (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2019)
Hypertension is a contributor to the second maternal death in Indonesia after bleeding and is still increasing every year. Hypertension in pregnancy is an increase in blood pressure systole above 140 mmHg and diastole above 90 mmHg on two measurements of five minutes intervals on the same arm in a state of adequate rest. This study aims to analyze the effect of ofDate palm feeding on changes in blood pressure on pregnant women getting hypertension. This study is a quasy experiment with pre-post test control design. The populations in this study were all pregnant women at Masyita Hospital and Kassi-Kassi PublicMedical Center, Makassar. The samples of 40 pregnant women were divided into intervention groups of 20 pregnant women and control of 20 pregnant women. The intervention group was given date palm for 30 days with a dose of 7 grains/day (100 gr/day), while the control group was given nutrition counseling for pregnant women. Data were analyzed using the Paired Samples Test and independent Samples Test. The results of the study on systole blood pressure measurements in the intervention group obtained p = 0,000, which means that there were significant differences before and after giving of Date palm. In the diastole blood pressure measurement in the intervention group, the p-value = 0,000 was obtained, which means that there were significant differences before and after giving of Date palm. Systole and diastole blood pressure in the control group obtained p = 0.163 and p = 0, 330, meaning that there were no significant differences before and after giving the education about the nutrition of pregnancy. It is concluded that there is an effect of Date palm feeding on changes in blood pressure on pregnant women getting hypertension in the Masyita Hospital and Kassi-Kassi Public Medical Center. It is expected that pregnant women routinely consume Date palm to avoid pregnancy hypertension.